2019
DOI: 10.1038/s42003-019-0532-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting p16-induced senescence prevents cigarette smoke-induced emphysema by promoting IGF1/Akt1 signaling in mice

Abstract: Senescence is a mechanism associated with aging that alters tissue regeneration by depleting the stem cell pool. Chronic obstructive pulmonary disease (COPD) displays hallmarks of senescence, including a diminished stem cell population. DNA damage from cigarette smoke (CS) induces senescence via the p16 pathway. This study evaluated the contribution of p16 to CS-associated lung pathologies. p16 expression was prominent in human COPD lungs compared with normal subjects. CS induces impaired pulmonary function, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 57 publications
2
42
0
Order By: Relevance
“…Many studies have reported that p53/p21 pathway activation is responsible for inducing cellular senescence (58)(59)(60). Furthermore, the activation of p16/pRb signaling is a vital indicator of senescence (58,61). This study demonstrated that paclitaxel suppressed the expression of p53, p21, hypophosphorylated pRb and p16, which might be linked to the elimination of cellular senescence of PC9-MET cells (Figure 7).…”
Section: Discussionmentioning
confidence: 55%
“…Many studies have reported that p53/p21 pathway activation is responsible for inducing cellular senescence (58)(59)(60). Furthermore, the activation of p16/pRb signaling is a vital indicator of senescence (58,61). This study demonstrated that paclitaxel suppressed the expression of p53, p21, hypophosphorylated pRb and p16, which might be linked to the elimination of cellular senescence of PC9-MET cells (Figure 7).…”
Section: Discussionmentioning
confidence: 55%
“…Employing Pathway Studio-guided "Shortest Path analysis" allowed us to explore plausible connections between these two genes and COPD, simultaneously highlighting a set of common interactors, which includes the signaling molecule and the pro-inflammatory cytokines. Among these, a connection of both TNFRSF12A and CD38 proteins to AKT1 is remarkable, as the stimulation of IGF1/AKT1 axis via the targeting of p16-induced senescence was recently shown to alleviate at least some phenotypic features of COPD (Cottage et al, 2019). Notably, among other connecting molecules are proinflammatory cytokines TNF-α, IL-1β, IFN-γ, and IL-6, which are the part of the SASP phenotype (Barnes, 2014;Ohtani, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, impaired immune responses characterised by reduced clearance capacity and higher susceptibility to infections are related to the accumulation of senescent T-lymphocytes and macrophages in COPD lungs [64]. Although studies depleting senescent cells using genetic models have generated conflicting results [79][80][81], the pharmacological depletion of senescent cells using the senolytic drug ABT-263 conferred resistance to elastase-induced emphysema in both young and aged mice [79].…”
Section: Regeneration Of a Diseased Lung Chronic Diseasesmentioning
confidence: 99%